Analiza wpływu dobrowolnego gromadzenia oszczędności emerytalnych na wysokość stopy zastąpienia - Wątorek, Bogumiła (The Impact of the Voluntary Retirement Savings on the Value of the Replacement Rate, 2008)
The main aim of this paper is to present an impact of the voluntary pension programmes on the overall replacement rate in a reformed pension system in Poland. Projections shown in this paper are based on the macroeconomic and demographic assumptions. The research results allow to indicate the main factors which have an influence on the replacement rate from the voluntary part of the pension system in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 458-466